2002
DOI: 10.1073/pnas.182418199
|View full text |Cite
|
Sign up to set email alerts
|

Specification of unique Pit-1 activity in the hGH locus control region

Abstract: The human GH (hGH) gene cluster is regulated by a remote 5 locus control region (LCR). HSI, an LCR component located 14.5 kb 5 to the hGH-N promoter, constitutes the primary determinant of highlevel hGH-N activation in pituitary somatotropes. HSI encompasses an array of three binding sites for the pituitary-specific POU homeodomain factor Pit-1. In the present report we demonstrate that all three Pit-1 sites in the HSI array contribute to LCR activity in vivo. Furthermore, these three sites as a unit are fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 27 publications
6
38
0
Order By: Relevance
“…All three Pit1 binding sites within the 404-bp fragment contribute to the LCR activity. Furthermore, these three Pit1 sites are sufficient to confer position-independent and somatotropes-restricted Ϫ0.5hGH-N transgene activation (261,262). In pituitary gland of transgenic mice carrying the intact hGH locus, ChIP assays reveal a 32-kb domain of pituitary-specific histone hyperacetylation extending from the LCR to the hGH-N promoter with peaks at HSI and HSII sites.…”
Section: Regulation Of Somatotrope/lactotrope Determinationmentioning
confidence: 99%
“…All three Pit1 binding sites within the 404-bp fragment contribute to the LCR activity. Furthermore, these three Pit1 sites are sufficient to confer position-independent and somatotropes-restricted Ϫ0.5hGH-N transgene activation (261,262). In pituitary gland of transgenic mice carrying the intact hGH locus, ChIP assays reveal a 32-kb domain of pituitary-specific histone hyperacetylation extending from the LCR to the hGH-N promoter with peaks at HSI and HSII sites.…”
Section: Regulation Of Somatotrope/lactotrope Determinationmentioning
confidence: 99%
“…If the transgene contains an insulator activity, it shows site of integration independent and copy-number dependent expression (Kellum and Schedl, 1991;Li et al, 2002b). Alternatively, when the transgene contained a strong enhancer activity, it could be expressed in a site of integration independent manner (Shewchuk et al, 2002). In case of the POP promoter, we could not detect any EGFP expression in four lines out of six (Table 1), which indicated that the transgene expression was dependent on its integration site.…”
Section: Discussionmentioning
confidence: 87%
“…To analyze the regulatory mechanism of transcription, a reporter gene assay is often used as a powerful technique, and it can uncover the in vitro activity of a regulatory sequence. However, to assess the in vivo activity, transgenic mice have to be generated and analyzed, and the result could be different from that of the reporter gene assay (Shewchuk et al, 2002). This is because a transgene is integrated into the mouse genome and influenced by the adjacent chromosomal environment in transgenic mice.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are other examples in which several enhancers that bind the same transcription factor are associated with a single target gene, in few cases are these enhancers as prevalent or as dispersed as seen in the Igf1 locus. For example, the mouse Rankl gene encodes some distal elements that bind c-fos (6), the ␤-hemoglobin locus contains sites for GATA transcription factors (35), and the GH locus, sequences for Pou1f1 (47), but these potential enhancers are fewer in number than the Stat5b elements in Igf1. As there appear to be no other genes within ϳ150 kb of rat Igf1 on chromosome 7q22 or within ϳ200 kb of human IGF-I on chromosome 12q23.2 (Ensemble release 78, December 2014), it seems reasonable to assume that these elements are involved primarily with Igf1 [although ENCODE data for several human cell lines indicate that only some identified interactions between distal elements and promoters map to the nearest gene from the element (46)].…”
Section: Discussionmentioning
confidence: 99%